Hadis Tentang Kesehatan dan Pengobatan Menggunakan Katak (Studi Analisis Sanad dan Pemahaman Hadis) - Naufal, Muhammad Bustanun Naufal (Al-Fath, 2023)
The frog being one of a kindamphibian which has many benefits and properties based on the nutritional content it has. The nutritional content contained in frogs has a role and can provide a balance to human nutrition, in 100 grams of frog meat there is a protein content that can be produced as much as 16.4 grams, this value is certainly quite large for amphibians, more than that the nutritional content Frogs also have other things, such as fiber, minerals, and vitamins, which the body needs sufficiently. Behind the benefits and efficacy of the nutrition contained in the frog there is a conflict with the provisions of Islamic law, namely in the form of a prohibition that the Prophet conveyed to kill frogs as contained in the history of Abū Dāud, which means that the hadith gives an indication in the form of a prohibition against consuming them too. However, in several areas in Indonesia, which are predominantly Muslim, they still have the habit of consuming frogs.